Access to Essential Cardiovascular Medicines in Pakistan: A National Survey on the Availability, Price, and Affordability, Using WHO/HAI Methodology - Saeed, Amna; Saeed, Faria; Saeed, Hamid; Saleem, Zikria; Yang, Caijun; Chang, Jie; Jiang, Minghuan; Zhao, Mingyue; Saqlain, Muhammad; Ji, Wenjing; Aziz, Muhammad Majid; Lambojon, Krizzia; et al. (Frontiers in Pharmacology, 2021)
Objective: This national survey was aimed at measuring the access to cardiovascular diseases (CVD) medicines in terms of their availability, price and affordability in Pakistan. This was done by using the standard WHO/ Health Action International (HAI) methodology. Methods: The price and availability data for 18 CVD medicines were collected from public sector hospitals (n=40) and private sector retail pharmacies (n=40) in eight cities of Pakistan. The outcome measures were availability (calculated as percentage of health facilities stocked with listed medicines), medicine price to the international reference price ratio i.e. median price ratio (MPR), and affordability (calculated as number of days’ wages (NDWs) of the lowest-paid unskilled government worker required to afford one month treatment of a chronic disease). The affordability of standard treatment in Pakistan with four CVD drugs was compared with data from six other LMICs using HAI database. Findings: The mean percent availability of CVD medicines was significantly low (p<0.001) in public sector as compared to the private sector, i.e., 25.5% vs 54.6% for originator brands (OBs) and 30.4% vs 34.9% for lowest price generics (LPGs), respectively. For all OBs and LPGs, the inflation adjusted mean MPR was 2.72 and 1, respectively. CVD medicines were found to be unaffordable with average NDWs of 6.4 and 2.2 for OBs and LPGs, respectively i.e. NDWs of more than 1. In international comparison with countries such as Sudan, Lebanon, Egypt, India, Afghanistan, and China, the affordability of standard treatment with selected CVD medicines (Atenolol, Amlodipine, Captopril, and Simvastatin) in Pakistan was found to be low. Overall, all four OBs and 3 out of 4 LPGs of selected CVD drugs were found unaffordable in Pakistan. Conclusion: These data indicated that the availability of selected CVD medicines was low in both public and private sector medicine outlets. Both OBs and LPGs were found unaffordable in private sector, necessitating the redressal of pricing policies, structuring, as well as their implementation.